PROSTHETIC IMPLANT MAP (PIM) - ACCURATE AND CONVENIENT ASSISTANT IN SUCCESSFUL IMPLANT TREATMENT - Neli Nikolova (Peytchinski Publishing, 2020)
Objective: This article presents a prosthetic map of implant dental treatment, which aims to systematize and archive the detailed information concerning the prosthetic aspect of implant treatment. Material and Methods: A survey about peri-implant soft tissues (PIST) was carried out among 31 dental practitioners experienced in implantology. Opinions were expressed about the significance of their specific characteristics in the creation of the implant supra-structure. A practical test for recognition of specific characteristics was performed by four dentists with a different level of experience in implant-supported prosthodontics, who have been thoroughly informed and instructed how to report the PIST status parameters in 10 implant sites. The analysed results were used as a base for the map criteria. Result: A prosthetic map was created with the following sections containing: 1) personal data with brief information about the patient, 2) information about the implant, 3) information about peri-implant alveolar bone, 4) information about PIST, 5) information about the planned implant restoration,6) information about follow-up examinations. Conclusion: The organization and formatting of the map allow very accurate marking of all data important for the implant prosthetic treatment and their follow-up over time. The Prosthetic implant map can be used as a guideline for implant supra-structure planning. From a practical point of view, it is a very convenient way of storing all the necessary information and its subsequent analysis for both clinician and patient.